2019
DOI: 10.1016/j.celrep.2019.07.066
|View full text |Cite
|
Sign up to set email alerts
|

Hantavirus Inhibits TRAIL-Mediated Killing of Infected Cells by Downregulating Death Receptor 5

Abstract: Highlights d HTNV induces TRAIL production by endothelial cells and NK cells d HTNV protects infected cells from TRAIL-mediated killing by downregulating DR5 d HTNV causes 26S proteasome-dependent degradation of DR5 and alters DR5 transport d HTNV infection leads to ubiquitination of DR5 and production of DR5 S

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 54 publications
1
18
0
1
Order By: Relevance
“…TNF-related apoptosis-inducing ligand (TRAIL)-death receptor 5 (DR5) signaling through TNFSF10–TNFRSF10B will activate IKK–JNK–MEK–MK2 in many nontransformed cells 100 . The multiplex kinase-activity fluctuations are consistent with the hypothesis that autocrine TRAIL-DR5 signaling is asynchronously downregulated in cardiomyocytes during CVB3 infection, as just reported for another single-stranded RNA virus 101 .…”
Section: Discussionsupporting
confidence: 89%
“…TNF-related apoptosis-inducing ligand (TRAIL)-death receptor 5 (DR5) signaling through TNFSF10–TNFRSF10B will activate IKK–JNK–MEK–MK2 in many nontransformed cells 100 . The multiplex kinase-activity fluctuations are consistent with the hypothesis that autocrine TRAIL-DR5 signaling is asynchronously downregulated in cardiomyocytes during CVB3 infection, as just reported for another single-stranded RNA virus 101 .…”
Section: Discussionsupporting
confidence: 89%
“…Clinical evidence has shown that HTNV infection is related to the upregulation of sTRAIL in HFRS patients (34,42). We document that HTNV infection leads to an increase of TRAIL expression in HUVECs, and TRAIL exhibits striking antiviral activities by inducing apoptosis in vitro.…”
Section: Discussionmentioning
confidence: 62%
“…Moreover, HTNV has also been shown to inhibit the extrinsic pathway of apoptosis through the downregulation of dead receptor 5, in a TRAIL-mediated mechanism activated by cytotoxic granules. 79 Despite the viral strategies to avoid the innate immune system, in the late stages of infection type I IFN Hantaviruses infect endothelial cells, monocytes and macrophages without cytopathic effect but producing an endothelial disruption. The detection of virions activates the immune response, with the primary production of cytokines from innate immune cells such as types I and III IFNs, IL-1b, TNF, IL-6 and IL-15, and chemokines such as CCL5 and CXCL10, among others.…”
Section: Hantavirus Recognition By Innate Immunitymentioning
confidence: 99%
“…78,84 Despite significant TRAIL upregulation in infected ECs and NK cells, HTNV-infected cells are protected by TRAIL-mediated killing, as previously discussed. 79 Moreover, inhibition of cell-mediated apoptosis has been observed in pathogenic and non-pathogenic hantaviruses, associated with NP-driven inhibition of granzyme B and caspase-3. 86 Those events would explain why infected ECs are not damaged despite strong cytotoxic lymphocyte activation in patients, according to the authors.…”
Section: Natural Killer Cellsmentioning
confidence: 99%